2010
DOI: 10.1088/1741-2560/7/4/046001
|View full text |Cite
|
Sign up to set email alerts
|

Self-aligned Schwann cell monolayers demonstrate an inherent ability to direct neurite outgrowth

Abstract: In vivo nerve guidance channel studies have identified Schwann cell (SC) presence as an integral factor in axonal number and extension in an injury site, and in vitro studies have provided evidence that oriented SCs can direct neurite outgrowth. However, traditional methods used to create oriented SC monolayers (e.g. micropatterns/microtopography) potentially introduce secondary guidance cues to the neurons that are difficult to de-couple. Although SCs expanded on uniform laminin-coated coverslips lack a globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…5). Neurite outgrowth has been reported to be directed by Schwann cell alignment in plane culture (Seggio et al, 2010;Thompson and Buettner, 2006). However, Schwann cells in this 3D culture system were aligned to the regenerating axons, which is quite different from the situation observed for 2D culture.…”
Section: Discussionmentioning
confidence: 56%
“…5). Neurite outgrowth has been reported to be directed by Schwann cell alignment in plane culture (Seggio et al, 2010;Thompson and Buettner, 2006). However, Schwann cells in this 3D culture system were aligned to the regenerating axons, which is quite different from the situation observed for 2D culture.…”
Section: Discussionmentioning
confidence: 56%
“…Methods including the use of neurotrophic factors (Meyer, Matsuoka, Wetmore, Olson, & Thoenen, 1992;Sendtner, Kreutzberg, & Thoenen, 1990), supportive cell grafts (e.g., SCs; Seggio, Narayanaswamy, Roysam, & Thompson, 2010) or stem cells (Zhang et al, 2010), autografts (den Dunnen & Meek, 2001), and artificial nerve conduits (Nectow, Marra, & Kaplan, 2012;Xu et al, 2003) have been shown to influence axon outgrowth and myelination both in vivo and in vitro. Methods including the use of neurotrophic factors (Meyer, Matsuoka, Wetmore, Olson, & Thoenen, 1992;Sendtner, Kreutzberg, & Thoenen, 1990), supportive cell grafts (e.g., SCs; Seggio, Narayanaswamy, Roysam, & Thompson, 2010) or stem cells (Zhang et al, 2010), autografts (den Dunnen & Meek, 2001), and artificial nerve conduits (Nectow, Marra, & Kaplan, 2012;Xu et al, 2003) have been shown to influence axon outgrowth and myelination both in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous strategies for promoting axon regrowth and remyelination following injury have been investigated. Methods including the use of neurotrophic factors (Meyer, Matsuoka, Wetmore, Olson, & Thoenen, 1992;Sendtner, Kreutzberg, & Thoenen, 1990), supportive cell grafts (e.g., SCs; Seggio, Narayanaswamy, Roysam, & Thompson, 2010) or stem cells (Zhang et al, 2010), autografts (den Dunnen & Meek, 2001), and artificial nerve conduits (Nectow, Marra, & Kaplan, 2012;Xu et al, 2003) have been shown to influence axon outgrowth and myelination both in vivo and in vitro. In addition, electrical stimulation (ES) has long been considered a potential method to enhance recovery in both the central nervous system (CNS) and the PNS (McCaig & Rajnicek, 1991;Thompson, Koppes, Hardy, & Schmidt, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The method proposed in this paper is a revised version of a well-established protocol in our laboratory 11 and it involves a direct contact between the two cell types (direct co-culture), in which the second cell type (DRG neurons) are seeded on the top of the others (SC-like ASC). This approach is based on previous findings that demonstrated the importance of the presence of a glial cell layer on the substrate when seeding neuronal cultures [35][36][37] . This effect is likely due to cell-cell interactions through DRG integrins and ECM molecules deposited from ASC and other cues on the stem cell surface.…”
Section: Discussionmentioning
confidence: 99%